An experience in the use of SCRUM and KANBAN for project development in a Waterfall environment - da Cruz, Eberth Felipe Castro; Fernandes Junior, Francisco Erivaldo; Sardinha, Eduardo Drumond (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2021: Anais do XX Simpósio Brasileiro de Qualidade de Software, 2021)
SIDIA R&D Institute is responsible for developing, validating, and localizing the Android Operating System (Android OS) used in smart devices, such as smartphones and tablets, sold in Latin American countries. Traditionally, SIDIA’s Model department is responsible for such development, and it is comprised of smaller teams working on individual Android components. For example, the Application team works on the Android’s System Apps layer, such as Photo Gallery and Phone Dialer. Like all Model’s teams, the Application employs the Waterfall methodology, a straightforward and widespread software development framework. However, the Application team can receive requests to work on projects unrelated to its primary activities. In these cases, the Waterfall methodology is unsuitable because it follows a linear pipeline [1], making it challenging to work on multiple and simultaneous projects. Hence, the present paper aims to report the experience of the Application team in transitioning from a pure Waterfall environment to a mix of Waterfall and Agile methodologies. Specifically, the team applied the SCRUM and KANBAN methodologies in four independent projects. The challenges caused by this culture change and the COVID-19 pandemic, which forced our workforce to work from home, are reported here. Furthermore, the team used Retrospective and Post-Mortem meetings to gather feedback from members about their experience with these new methodologies.